2015
DOI: 10.1038/ki.2014.424
|View full text |Cite
|
Sign up to set email alerts
|

Update on endocarditis-associated glomerulonephritis

Abstract: Glomerulonephritis (GN) due to infective endocarditis (IE) is well documented, but most available data are based on old autopsy series. To update information, we now present the largest biopsy-based clinicopathologic series on IE-associated GN. The study group included 49 patients (male-to-female ratio of 3.5:1) with a mean age of 48 years. The most common presenting feature was acute kidney injury. Over half of the patients had no known prior cardiac abnormality. However, the most common comorbidities were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
183
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(197 citation statements)
references
References 45 publications
7
183
0
7
Order By: Relevance
“…As with CG, a membranoproliferative-pattern GN with IgG and C3 deposition is the traditional pattern of injury for IE. However, a recent study of clinical specimens demonstrated that IE presented most commonly with crescentic GN, followed by diffuse proliferation, and finally mesangial proliferation without endocapillary proliferation or crescent formation, the latter of which was seen in this case [13]. Confounding this case if the presence of dominant IgM staining in addition to C3.…”
Section: Discussionmentioning
confidence: 52%
“…As with CG, a membranoproliferative-pattern GN with IgG and C3 deposition is the traditional pattern of injury for IE. However, a recent study of clinical specimens demonstrated that IE presented most commonly with crescentic GN, followed by diffuse proliferation, and finally mesangial proliferation without endocapillary proliferation or crescent formation, the latter of which was seen in this case [13]. Confounding this case if the presence of dominant IgM staining in addition to C3.…”
Section: Discussionmentioning
confidence: 52%
“…3,5,911,26,27,47 The presence of c-ANCA in infectious endocarditis is unclear: it may represent a false-positive or related to the infection or the production of c-ANCA may be induced through B-cell activation after release of PR-3 from neutrophils. 43,48 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ANCA positivity was seen in 28% of patients in this cohort. 48 Glomerulonephritis occurs by 2 main immunologic mechanisms: immune complex–mediated and ANCA-associated or pauci-immune. The commonest type of glomerulonephritis is vasculitic, with minimal to absent staining for immunoglobulins by immunofluorescence in 63% to 69% of patients with endocarditis-associated glomerulonephritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Les principales pathologies responsables de GnRP observées en réanimation sont les vascularites associées aux ANCA, la maladie de Goospasture, le lupus et les glomérulo-néphrites associées aux foyers infectieux profonds, qui compliquent le plus souvent l'évolution des endocardites [11].…”
Section: Glomérulonéphrites Rapidement Progressives (Gnrp)unclassified